Ultrasound findings in tendons and ligaments of lame sport horses competing or training in South Florida venues during the winter seasons of 2007 through 2016. (15th May 2020) - Mitchell, R. D.; DaSilva, D. D.; Rosenbaum, C. F.; Blikslager, A. T.; Edwards, R. B.
Summary: Knowledge of common soft tissue lesions in sport horses in training should prove beneficial for evaluating lameness and developing training and management regimens to avoid injury and aid rehabilitation. Medical records were reviewed from 2007 to 2016 to describe tendon/ligament lesions in lame sport horses training and competing at the same venues during the winter show circuit and identified by lameness and ultrasonographic examinations. Season, discipline, breed, age, gender, limb and ultrasound findings were recorded. Descriptive statistics were used to describe the population of horses. Significance of association of gender, discipline and limb with lesion type was evaluated using chi‐squared analyses. Values were considered significant at P ≤ 0.05. Lesions were identified in 296 horses: 176 dressage and 120 hunter/jumpers. Ninety‐two horses (31%) had multiple lesions. Suspensory ligament lesion locations (n = 281) were categorised as proximal (n = 144), body (n = 22) and branches (n = 115). Superficial digital flexor tendon (SDFT; n = 37), deep digital flexor tendon (DDFT; n = 27), inferior check ligament (ICL; n = 34), digital flexor tendon sheath (n = 17), distal sesamoidean ligament (n = 10), lower limb collateral ligament (n = 14), carpal sheath (n = 2), superior check ligament (n = 2) and tarsal sheath (n = 1) lesions were noted. Remaining lesions identified were medial branch SDFT (n = 2), lateral branch SDFT (n = 2), palmar annular ligament (n = 3), lateral plantar ligament (n = 2) and inter‐sesamoidean ligament (n = 1). Rear limb proximal suspensory abnormalities, specifically the right hindlimb (n = 68), were significantly over‐represented (P = 0.03). Suspensory origin, suspensory branch, ICL, SDFT and DDFT accounted for 82% of the abnormal findings identified. SDFT, DDFT and ICL lesions were most often identified in the front limb. The lesion type and location may provide insight in assessing training regimens, patient monitoring and rehabilitation guidelines.